Building Data Collection Information System in the Papua Province Building and Environmental Arrangement Work Unit - Muhammad Taher Jufri; Mursalim Tonggiroh; Arga Permana Reysamputra (IAIC International Conference Series, 2020)
The Papua Province Environmental and Building Arrangement Work Unit is still carried out conventionally in carrying out building data collection. Data collection is still using a questionnaire form, then entered into a computer using Microsoft Excel. This study aims to build an online building data collection information system. Data obtained through direct observation on the object of research and interviews with the building data collection field. The analytical method used to analyze problems in the ongoing system is the PIECES analysis method. The design is carried out using an object-oriented design method, namely, UML design. And the system testing stage uses the black box method. With the existence of an online building data collection information system, it is expected to be a solution to simplify and speed up the process of the survey team conducting building data collection.